Architectural wood remains and climatic variations in early 2nd millennium CE, northwest Alaska: reflections on the possibilities and limits of Dendroarchaeology - Juliette Taïeb (IdeAs)
Architectural wood elements are well-preserved in cold soils and archaeological Thule/Iñupiat sites of the early 2nd millennium CE in northwestern Alaska. These organic remains, at the intersection of archaeology, palaeoclimatology, and ecology, offer an annual and local resolution rarely accessible to archaeologists, providing insights on past climate variations. In a context where cultural variations of past arctic people are often interpreted as responses to climatic and environmental changes, this paper is a state-of-the-art examination of the dendroclimatic potential of Iñupiat architectural wood remains based on current knowledge. The focus is especially on current possibilities and limits of early Iñupiat architectural wood remains and the need to build a finer sequence for the period of the Medieval Climate Anomaly [MCA] (9th-13th century) to contribute to a broader understanding of the climatic framework of the early 2nd millennium and of early Iñupiat socio-ecological dynamics in Northwest Alaska for future research.